Wage inequality's decreasing effect on enterprise operating revenues - Jarle Aarstad; Olav Andreas Kvitastein (Economies, 2023)
This study assesses whether wage inequality affects enterprises' operating revenues and whether operating revenues reversely affect wage inequality. To study our research questions, we analyze panel data from Norway and find that wage inequality decreases operating revenues. I.e., increasing high earners' wages relative to those earning low ones-or decreasing low earners' wages relative to those earning high ones-decreases operating revenues. It implies that wage inequality is detrimental to enterprise performance. Reversely, decreasing operating revenues increases wage inequality. I.e., low earners' wages are reduced relatively more than those earning high ones when enterprise revenues decrease. Increasing operating revenues, on the other hand, does not decrease wage inequality.
Keywords: 330; dynamic unconditional quasi-maximum likelihood panel regression; dynamic GMM panel regression; instrumental variables